ORGANIZATIONAL CULTURE : ARE YOU REALLY THE ONE ? - Zebua, Martin; Fatimah, Nuzulul; Zargar, Nasir Ahmad (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The condition of a healthy organization cannot be determined solely by the condition of its assets or the appearance of its resources. There are numerous factors that owners and potential investors must take into account. There are often hidden aspects that should be of concern to both owners and external parties interested in becoming investors. In the service sector, the key factors for growth and development are the quality of service provided and the capabilities of the human resources. However, the financial aspect also plays a significant role in the growth and development of a service organization. This qualitative article aims to provide concrete evidence that service organizations face challenges in their growth and development when their service activities fail to meet consumer expectations or even harm them. Consumers act as unpaid marketers for organizations engaged in service activities. Once an organization disappoints its consumers, news of the poor service spreads quickly in the market. Consequently, it is inevitable that the organization will experience a decline in its market share in the near future.